Nutrition Education Effect on Anemia Incidence in Female Adolescents: Meta-Analysis for Future Health Post-COVID-19 Pandemic - Rahmiwati, Anita; Djokosujono, Kusharisupeni; Krianto, Tri; Utari, Diah Mulyawati; Djuwita, Ratna; Utama, Feranita (UI Scholars Hub, 2023)
Female adolescents are at a heightened risk of anemia due to inadequate iron intake and absorption, blood loss during menstruation, and an escalated need for iron to support rapid growth. This study examined the impact of nutrition education on the incidence of anemia in adolescent girls. The investigation was conducted through a systematic review and meta-analysis, employing articles from reputable sources such as Google Scholar, JAMA Network, PubMed, ScienceDirect, The New England Journal of Medicine, Lancet, and ProQuest, published between 2013 and 2021. The keywords for data retrieval were